The Study of Oral Findings, Oxidative Stress and Antioxidant Vitamin E in Serum and Saliva of Crohn's Patients on Azathioprine Monotherapy and those on Combination of Anti-TNF-Î± Plus Azathioprine - Abbas, Zainab Kh.; Zaidan, Taghreed F. (Journal of Baghdad College of Dentistry, 2018)
Background: Crohn's disease (CD) is an immunological disorder associated with chronic inflammatory process of several unspecific regions of gastrointestinal tract but frequently detected in the terminal Ilium and proximal colon or both. This disease frequently presented with various oral manifestations as a consequence of inflammatory process of the disease, nutritional deficiency or medications side effects. Several therapeutic approaches have been developed for CD management that are targeting the inflammatory process and directed at controlling the host immune response. Immunosuppressants such as Azathioprine and anti-TNF Î± agents as well as the combination of them have been widely used as an effective therapeutic modality with a better chance of achieving clinical remission and decrease the risk of future complications.Subjects, Materials, and Methods: Seventy-five subjects were incorporated in this study; fifty subjects presented with moderate to severe CD that were subdivided into two subgroups treated with different therapeutic modalities( Azathioprine monotherapy and Combination of anti TNF-Î± biological agent (Infliximab) plus Azathioprine), while other twenty-five were age and gender matched healthy control subjects. Body mass index (BMI) of all participants was determined by weight (kg)\ high (m2). Oral cavity of each patient was examined for the presence of oral manifestations. Blood and saliva samples were gained from each subject enrolled in this study and salivary flow rate (ml\min) was measured for those participants, then these samples were centrifuged and the supernatants frizzed for subsequent oxidative stress and antioxidants biomarkers assessment.Results: The means of BMI and salivary flow rate were significantly higher in combination treated group than Azathioprine treated group. Fungal infection was the main oral findings that observed among Crohn's patients on combination therapy compared with those on Azathioprine monotherapy. Assessment of oxidative stress and antioxidant activity revealed that the means of serum and saliva Malondialdehyde (MDA) were highly significantly higher in Azathioprine treated group than combination treated group, while Vitamin E (VE) level showed significant reduction in Azathioprine Crohn's group as compared to combination treated group. Significant negative linear correlation was found between MDA level in serum and saliva with duration of treatment, while highly significant positive correlation was detected between VE levels and duration of treatment.Conclusions: Oxidative stress was increased with reduced antioxidant level in both groups of Crohn's patients. Treatment with Combination therapy approved to be effective in controlling oxidative tissue damage and enhanced antioxidants system in Crohn's patients better than Azathioprine monotherapy. Fungal infection was the most predominant oral manifestations among Crohn's patients on combination therapy as a result of concomitant immunosuppressive effect that accounted for reduced immune response to opportunistic infections.